2019
DOI: 10.1590/1981-863720190004020180038
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic analysis the obturation’s quality in root canal treatment performed by a South Brazilian sample of undergraduate students

Abstract: Objective to investigate the quality of root canal treatments performed by undergraduate students. Methods 274 root-filled teeth (excluding molars) from the Department of Endodontology of the Federal University of Santa Catarina in a nine-year period were selected and evaluated by two calibrated examiners. The evaluation was based on tooth type, number of root canals, presence or absence curvature, length of filling material considered the radiographic apex as reference (considered adequate shorter than 2mm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(41 reference statements)
2
3
2
2
Order By: Relevance
“…The quality assessment of the endodontic treatment carried out by dentistry students as well as GPDs and endodontists was evaluated in the literature [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality assessment of the endodontic treatment carried out by dentistry students as well as GPDs and endodontists was evaluated in the literature [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, not only the extrusion of gutta-percha cones but also any amount of sealer beyond apex was considered as overfilling. Various studies have investigated the radiographic quality of root canal fillings performed by clinical dental students [ 17 , 37 , 38 , 39 , 40 , 41 ]. In this research, the adequate length and density of RCT performed by 4th-year students were found in 81.71% and 92.86%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos pacientes era do sexo feminino (65,0%) corroborando com os resultados de Occhi et al 17 , Soares 13 , Ferreira et al 18 e Siqueira Jr et al 6 que obtiveram maior prevalência deste gênero em 75%, 69,9%, 72,8% e 66,3%, respectivamente. Nesse estudo, a faixa etária mais prevalente foi entre 21 e 30 anos, 24,4% do total da amostra, com média de idade dos pacientes atendidos de 35,07 anos, variando de 12 a 67 anos.…”
Section: Discussionunclassified
“…Esse trabalho evidenciou que o grupo dentário mais prevalente foi o dos Incisivos centrais superiores com 23,6% do total da amostra. Estes valores concordam com os de Soares 13 , Ferreira et al 18 e Ribeiro et al 19 que obtiveram 25,8%, 49% e 49,6% respectivamente, de prevalência por tal grupo dentário. Entretanto, diferem dos resultados encontrados por Siqueira Jr et al 6 , onde a maior prevalência foi de pré-molares superiores (20,6%), e dos resultados de Zoti e Hartmann 2 e Eskandarloo et al 3 , que encontraram a maior prevalência no grupo dos pré-molares em 37,8% e 45,1% dos casos analisados, respectivamente.…”
Section: Discussionunclassified
“…However, root canal treatment is very challenging and technically demanding, as well. A high rate of poor quality obturation (25-62%) and a high percentage of apical periodontitis associated with root-filled teeth (45%) have been observed in various studies [5][6][7]. Additionally, malpractice claims in endodontics are most commonly associated with technical 1 complications and mishaps [8].…”
Section: Introductionmentioning
confidence: 99%